TANZİMAT DÖNEMİ TÜRK ŞİİRİNDE KOPUŞ, SÜREKLİLİK, YENİLİK - ÜNLÜ, FATIMA RAVZA (Fırat Üniveristesi, 2025)
Bu çalışma Tanzimat dönemi Türk şiirinin geleneksel ve yenilik açısından değerlendirilmesi üzerine yapıldı. Batı medeniyetini tanımaya başlayan Tanzimat aydını sosyal ve siyasi gelişmelerle birlikte edebiyatını da yakından takip eder. Klasik şiirin etkisinde gelişen Türk edebiyatı Batı edebiyatının etkisinde yeniden şekillenir. Tanzimat dönemi Türk şiiri bu dönemde bir yandan gelenekten diğer yandan Batı şiir anlayışından beslenir. Bu nedenle de Tanzimat şiirinde kopuş, süreklilik ve yenilik bir aradadır. Tanzimat şairinin değişen zihniyeti şiirin muhtevası ve şekil anlayışını da etkiler. Klasik şiirde olduğu gibi, Tanzimat şiiri de Allah ve âlem algısında tasavvufî düşüncelerden yararlanır. Söz konusu tasavvufî düşünceler Allah'ın yaratmasıyla ilgili olan sudûr, işrâk ve vahdet-i vücut gibi nazariyeler etrafında şekillenir. Kaside ve gazel formuyla da ilişkili olan bu nazariyeler geleneğin şekil ve kelime kadrosunun etkisiyle süreklilik, Batı medeniyetinin etkisiyle de kopuş ve yenilik gösterir. Tasvvufî düşüncenin günlük hayata pratik çözümler sunamadığı gerçeği şiirde düşüncenin, bilginin önem kazanmasına yol açar. Klasik şiirin miskin yapısının aksine Tanzimat şiirinin dinamik yapısı şiir bünyesinde gelişen 'hâl' değişikliğini açığa çıkarır. Geleneğin tasavvufî düşünce ve mazmunlar etrafında gelişen 'uçlarda hâllerinin' yerini yeniliğin mücadeleci ve tenkit edici dinamik hâlleri alır. Aynı zamanda geleneksel şiirin formu tahrip eden anlayışının aksine Tanzimat şiirinin eşyayı ve tabiatı gerçekliğiyle kabullenmesi şiirde özdeşleşme hâlinin de yönünü değiştirir. Gelenekli şairden farklı olarak Tanzimat şairi 'ben' ve 'o' ayrımını kesin bir dille belirtir. Klasik şiirin asırlar boyu süren güçlü yapısını bir kere de kırmak Tanzimat şairi için mümkün olmaz. Şekil, vezin, kafiye, söz sanatları gibi önemli unsurların beyit bağlamındaki sarsılmaz birlikteliği kelime seçimini doğrudan yönlendirir. Tanzimat şairleri halka yönelmek adına şiirde sade bir dil kullanmayı arzulasa da geleneksel şiirin kalıplaşmış kuralları bu duruma müsade etmez. Tanzimat şairleri, duygu ve düşüncelerini daha rahat ifade edebilmek adına vezin ve kafiyede esneklik gösterme yoluna giderler. Klasik şiirin 'tenevvü' temelli kuralcı yapısına karşı 'tevsi', 'teressüm', 'tecessüm' gibi yeni teknikler şiirde görülür. Şiirde uygulanan yeni teknikler ile beyit düzenine bağlı kalmak yerine mısra serbestliğine yönelmek şairlere bireysel duygu ve düşüncelerini daha açık bir şekilde ifade etme imkânı sağlar. Bu bağlamda Şinasi'nin başlatmış olduğu yenilik adımını Namık Kemal, Ziya Paşa, Recaizade Mahmut Ekrem ve Abdülhak Hamid Tarhan daha da ileriye taşır.

This study focuses on evaluating Turkish poetry of the Tanzimat period in terms of tradition and innovation. The Tanzimat intellectuals, who began to become acquainted with Western civilization, closely followed its literature and social and political developments. Turkish literature, having broken away from the influence of classical poetry, was reshaped by Western literature. Turkish poetry of the Tanzimat period drew inspiration from both tradition and Western poetic sensibilities. Therefore, break, continuity, and innovation coexist in Tanzimat poetry. The changing mindset of Tanzimat poets also influenced the content and form of their poetry. Like classical poetry, Tanzimat poetry also draws upon Sufi thought in its perception of God and the universe. These Sufi ideas are shaped by theories of God's creation, such as emanation (sudûr), illumination (ishrâk), and the unity of existence (wahdat al-wujud). These theories, which are also related to the qasida and ghazal forms, show continuity under the influence of the tradition's form and vocabulary, while also exhibiting rupture and innovation under the influence of Western civilization. Sufi thought cannot offer practicalsolutions to daily life. In response to this situation, thought and knowledge take on greater importance in poetry. In contrast to the sluggish structure of classical poetry, the dynamic structure of Tanzimat poetry reveals the changing 'state' that develops within the poem. The 'bicuspid states' of tradition, which developed around Sufi thought and metaphors, are replaced by the combative and critical dynamic states of innovation. At the same time, in contrast to the traditional poetic approach that destroyed form, the Tanzimat poetry's acceptance of objects and nature as they are changes the direction of identification in poetry. Unlike traditional poets, Tanzimat poets clearly distinguish between 'subject' and 'object'. It would be impossible for a Tanzimat poet to break the powerful structure of classical poetry, which had endured for centuries, all at once. The unwavering unity of key elements such as form, meter, rhyme, and figures of speech within the context of a couplet directly guides word choice. Although Tanzimat poets sought to use simple language in their poetry to appeal to the public, the conventions of traditional poetry did not allow it. Tanzimat poets adopted a flexible approach to meter and rhyme, allowing them to express their feelings and thoughts more freely. In contrast to the rigid, rule-bound structure of classical poetry based on 'variety', new techniques such as 'expansion', 'portrayal', and 'embodiment' are seen in poetry. New techniques applied in poetry, such as moving away from the traditional couplet structure towards free verse, allow poets to express their individual feelings and thoughts more openly. In this context, Şinasi's innovative step was further advanced by Namık Kemal, Ziya Paşa, Recaizade Mahmut Ekrem, and Abdülhak Hamid Tarhan.
Break, continuity, and innovation in Turkish poetry of the Tanzimat period
Keywords: Türk Dili ve Edebiyatı